TINGKAT PENGETAHUAN LANSIA TENTANG ASAM URAT PADA LANSIA DI PUSKESMAS BINJAI ESTATE TAHUN 2020 - Siregar, Ilham Syahputra (JURNAL HEALTH REPRODUCTIVE, 2021)
Uric acid or gouty arthritis is the result of the final metabolism of purines, which are a component of nucleic acids found in the nucleus of body cells. Increased levels of uric acid can cause disturbances in the human body such as aches and pains in the joints and are often accompanied by extreme pain for the sufferer. The purpose of this study was to determine the extent of the elderly's knowledge of gout at the Binjai Estate Health Center. This research was carried out with a descriptive type of research and using a total sampling technique, a sample of 35 respondents covering age, education, and occupation. Data were collected from respondents using a questionnaire containing questions about gout. The data is then presented in the form of a frequency distribution table using the formula P = f/n x 100%. The results of the percentage and scoring of the research are interpreted using the good category 79% - 100%, the sufficient category 56% - 78%, and the less category <56%. From the results of research conducted by researchers regarding the description of respondents' knowledge about gout with the majority of respondents with less knowledge as many as 13 respondents (37%). It is necessary to increase the knowledge of the elderly about gout from direct or indirect information so that the knowledge of the elderly increases and is better.